Improvement of the organizational and economic mechanism of public-private partnership in the sphere of higher education - Khakimov Temur Tora oglu (THE INNOVATION ECONOMY, 2026)
This article analyzes the current state of public-private partnership (PPP) mechanisms in the higher education system and proposes organizational and economic improvements. The experience of developed countries has been studied, and the role of PPP in sustainable financing of higher education in Uzbekistan is revealed.